Policy changes in times of crisis: Evidence from the Arab Spatial Policy Analyzer - Bordignon, Jacopo; Breisinger, Clemens (International Food Policy Research Institute, 2015)
The paper introduces and demonstrates different uses of the Arab Spatial Policy Analyzer (ASPA), a new online policy database for the analysis of food and nutrition security in the Middle East and North Africa region. Using the ASPA database, we assess the nature of policy activity throughout the Arab region, specifically during the 2008 global food price crisis and the 2011 social uprisings. The ASPA is a means for identifying broadly those policy areas where governments are active and can help analysts, researchers, and decisionmakers discern what policy actions governments are undertaking to bring about stability and prosperity for their people. The ASPA database draws from a variety of sources: country reports of the Economist Intelligence Unit; datasets of the World Bank Food Price Crisis Observatory, the FAO Food and Agriculture Policy Decision Analysis Tool, and FAOLEX Legal Office; and the Global Agriculture Information Network reports of the US Department of Agriculture’s Foreign Agriculture Service. The database has several distinct features when compared to other policy monitoring tools, including a novel policy classification system and policy directions indicating either an increasing or decreasing value for determinate policy instruments—for example, an increase in food subsidies. We find that in times of crisis governments in the Middle East and North Africa region focus on “firefighting” policies that neglect both fiscal prudence and interventions with more impact, such as investments in infrastructure and targeted social protection measures.